Morphological Proses of Wolio Language in Kabanti Nuru Molabi - Nurhayati Nurhayati (Hasanuddin University, 2021)
Morphology is the study of words and their structure. Morphological process is a mean of changing a stem to adjust its meaning to fit its syntactic and communicational context while morphological system of language reveals its properties trhough the morphemic structur of words. This research is aimed to elaborate the morphological system of Wolio language in Kabanti Nuru Molabi based on Anceaux theory. Kabanti is an oral tradition in literary works. Descriptive method is used to analyze this research. To do this research, the researchercollect the data from Kabanti Nuru Molabi text. Moreover, in this theory, Anceaux proposed and devided the morphological system based on the class of words. One same prefix is possible to make a different class of wordswhen it is attached to a verb or a noun. Anceaux classified the morphem based on the stem attached to verb or noun. Nevertheless, the data in Kabanti Nuru Molabi shows that suffix –na, to form a possessive, and suffix –mo to form demonstrative or affirmation are not covered in Anceaux.